A Comparisonal Study on Unbalance Failure in the Perspective of Vibration and Electrical Consumption Analysis - Salih Seckin Erol (International Journal of Applied Methods in Electronics and Computers, 2016)
In this research, condition of resonance effect which is a common problem for mechanical constructions has been studied in perspective of unbalance failure of a bearing. A test setup designed respect to case practices; constructed and located in laboratory conditions. A bearing in the electrical motor, that is one of the elements in the test setup, has been selected for gathering data in vibration and electrical consumption during the test. The purpose of the research is testing condition of unbalance failure and resonance for studying comparison in various predictive maintenance approaches. Test has been implemented under the electricity frequency of 40.5 Hz that induced the electrical motor for determining rotational speed. According to the analysis results, inspecting of unbalance failure and resonance problem has been detected more clearly by vibration analysis.